Does the Endodontic Education Level Affect Decision-Making for Endodontically Treated Teeth With Apical Periodontitis? A Web-Based Survey - Betul Aycan Alim-Uysal; Asiye Nur Dincer; Berkan Yurtgezen; Mehmet Burak Guneser (Elsevier, 2021)
Objectives: The management of endodontically treated teeth with apical periodontitis is debated among clinicians. The aim of this study was to evaluate treatment choices for endodontically treated teeth with different sizes of periapical lesions among endodontists, endodontics postgraduate students, general dental practitioners, and undergraduate students who had fulfilled their theoretical and clinical training in endodontics. Materials and Methods: Periapical lesion images (no periapical lesion and 1-mm, 3-mm, and 5-mm periapical lesions) were formed on 4 different radiographs with a software program, and the survey included 16 radiographs that were emailed to 1881 participants. Treatment options included extraction, surgical or nonsurgical retreatment, and wait and see. The χ2 test was used to compare the responses of the participants. Results: The survey was returned by 1039 participants (55.23%). There were statistically significant differences among the responses of all participants for all cases (P < .05), except a case with a broken file and no lesion (P = .918). All participants decided to extract at an increased size from a 1-mm periapical lesion to a 5-mm periapical lesion. At all lesion sizes, general dental practitioners planned retreatment less when compared with other groups. Conclusions: This survey study showed that there was a positive correlation between endodontic education level and retreatment decision-making. Dentists who confront seemingly hopeless endodontically treated teeth such as an instrument fracture, a missing canal, or a large periapical lesion should consult with an endodontist before making the decision to extract the tooth.